Representasi Bencana Tsunami di Aceh dalam Puisi W. Suroso dan Dinullah Rayes - Assilmy, Maulia; Rahmah, Aulia; Ilmi, Fathya Madinatul (Journal of Education Language and Innovation, 2024)
Literary works can describe various human and natural phenomena. Disasters appear as a topic of conversation that cannot be separated from the themes of literary works. One of the places where disasters appear in literary works is Indonesia. The country's natural geographical and demographic conditions become a reference for the publication of creative works. The tsunami disaster is an interesting topic to discuss. This research uses comparative literary studies, which aims to describe the results of a comparison of two poems from two poets. The data analysis method uses a qualitative descriptive method. This research describes the results of a comparison of the meaning and analysis of intrinsic elements in the poem Prahara Langit Prahara Bumi by Dinullah Rayes and the poem Prahara at the End of the Year by Wiyanto Suroso using sentences of appreciation for the meaning and intrinsic elements. The data source used in the research is from a collection of books. a poem by an Indonesian poet who commemorates the tragedy of the Aceh tsunami disaster, entitled Duka Aceh Luka Kita. The data results found in the similarities contained five data; in the differences, there were 2 data.